Question
upstudy study bank question image url

Solve: \( \frac{5}{a-1}+\frac{2}{a-7}=\frac{a^{2}+4 a-65}{(a-1)(a-7)} \) \( a=\square \) (Enter your answer(s), separated by a comma, or DNE if there is no solution)

Ask by Vaughn Washington. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( a = -4 \)

Solution

Solve the equation \( \frac{5}{a-1}+\frac{2}{a-7}=\frac{a^{2}+4a-65}{(a-1)(a-7)} \). Solve the equation by following steps: - step0: Solve for \(a\): \(\frac{5}{a-1}+\frac{2}{a-7}=\frac{a^{2}+4a-65}{\left(a-1\right)\left(a-7\right)}\) - step1: Find the domain: \(\frac{5}{a-1}+\frac{2}{a-7}=\frac{a^{2}+4a-65}{\left(a-1\right)\left(a-7\right)},a \in \left(-\infty,1\right)\cup \left(1,7\right)\cup \left(7,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{5}{a-1}+\frac{2}{a-7}\right)\left(a-1\right)\left(a-7\right)=\frac{a^{2}+4a-65}{\left(a-1\right)\left(a-7\right)}\times \left(a-1\right)\left(a-7\right)\) - step3: Simplify the equation: \(7a-37=a^{2}+4a-65\) - step4: Move the expression to the left side: \(7a-37-\left(a^{2}+4a-65\right)=0\) - step5: Subtract the terms: \(3a+28-a^{2}=0\) - step6: Factor the expression: \(\left(7-a\right)\left(4+a\right)=0\) - step7: Separate into possible cases: \(\begin{align}&7-a=0\\&4+a=0\end{align}\) - step8: Solve the equation: \(\begin{align}&a=7\\&a=-4\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&a=7\\&a=-4\end{align},a \in \left(-\infty,1\right)\cup \left(1,7\right)\cup \left(7,+\infty\right)\) - step10: Find the intersection: \(a=-4\) The solution to the equation is \( a = -4 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \[ \frac{5}{a-1}+\frac{2}{a-7}=\frac{a^{2}+4 a-65}{(a-1)(a-7)}, \] we can start by finding a common denominator for the left side. The common denominator is \((a-1)(a-7)\). Rewriting the left-hand side gives: \[ \frac{5(a-7) + 2(a-1)}{(a-1)(a-7)} = \frac{5a - 35 + 2a - 2}{(a-1)(a-7)} = \frac{7a - 37}{(a-1)(a-7)}. \] Now, we set the numerators equal to each other since the denominators are the same: \[ 7a - 37 = a^2 + 4a - 65. \] Rearranging gives: \[ 0 = a^2 - 3a - 28. \] Factoring this quadratic equation: \[ 0 = (a - 7)(a + 4). \] Setting each factor to zero gives us the solutions: \[ a - 7 = 0 \quad \Rightarrow \quad a = 7, \] \[ a + 4 = 0 \quad \Rightarrow \quad a = -4. \] However, we must check for any extraneous solutions by substituting back into the original denominators: - For \(a = 7\), the term \(\frac{5}{a-1} = \frac{5}{6}\) is valid but \(\frac{2}{a-7}\) becomes undefined since the denominator is zero. - For \(a = -4\), both denominators are valid: \(\frac{5}{-5} = -1\) and \(\frac{2}{-11} = -\frac{2}{11}\), hence valid. Thus, the only valid solution is: \[ a = -4. \] So the answer is \( a = -4 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy